Helping Students Acquainted with Multiplication in Rectangular Model - Fridgo Tasman; Jaap den Hertog; Zulkardi Zulkardi; Yusuf Hartono (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
Usually, multiplication is introduced to students to represent quantities that come in group. However there is also rectangular array model which is also related to multiplication. Barmby et al (2009) has shown that the rectangular model such as array representations encourage students to develop their thinking about multiplication as a binary operation with row and column representing two inputs. Considering that finding, this study focusses on a design research that was conducted in Indonesia in which I investigate second grade studentsâ€™ (between 7 and 8 years old) in Madrasah Ibtidaiyah Negeri (MIN) 2 Palembang, Indonesia, ability to structuring the situation and their ability to represent rectangular model into multiplication sentence. The results shows us that students activity to structuring the situation, looking the number of objects in row or in column, lead them to repeated addition and transform it into multiplication sentence.Keywords: Rectangular pattern, MultiplicationÂ DOI: http://dx.doi.org/10.22342/jme.2.2.747.185-198